Book review Jünger E. Fire and Blood / Translation from German by A. Andrievsky. – Kyiv: Anna Klokun Publisher, 2018. – 336 p. - B. E. Nosenok, (Ukrainian Cultural Studies, 2019)
"Fire and Blood": (Re)discovering Ernst Jünger